Pelayanan Informasi dan Konseling oleh Apoteker tentang Penyakit Degeneratif serta Pemeriksaan Kesehatan kepada Masyarakat di Desa Ndokum Siroga: Information and Counseling Services by an Apothecary about Degenerative Diseases and Health Checks to the Community in Ndokum Siroga Village - Hafid Syahputra; Aminah Dalimunthe; Nazliniwaty Nazliniwaty; Lisda Rimayani Nasution (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Degenerative disease is a disease experienced by many people, such as hypertension, coronary heart disease, diabetes mellitus, gout, and others. Pharmacists play a role in providing information and education about health, primarily pharmacological and non-pharmacological drugs. The purpose of the activity is to increase public understanding regarding degenerative diseases from the side of treatment by pharmacists by adopting a healthy lifestyle and understanding the importance of health checks as the first step to early detection of degenerative diseases. The implementation method is in the form of health checks in the form of blood pressure, cholesterol, uric acid, and blood sugar levels so that it can be early detection of degenerative diseases. Information and counseling services by pharmacists regarding healthy lifestyles and information related to treatment and degenerative diseases using brochures and individual direct delivery. The activity was carried out in Ndokum Siroga Village, Karo Regency. The service results were carried out at the village hall with 35 participants. The activity was full of enthusiasm, and many questions arose during the service by the pharmacist. It is known that participants' understanding of degenerative diseases is very low, with only 24% who know about degenerative diseases, 32% who know the symptoms of the disease, 27% who know the risks, and 30% who apply preventive and promotive efforts. 14% of participants do not know that they have the degenerative disease, so it can be concluded that this activity is very helpful and provides good benefits to the community.